KAjIAN EFEKTIVITAS PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPEJIGSAWDAN STAD·PADA MATA PELAjARAN IPA ASPEK KIMIA DI SMP2 MLATISLEMAN - Fajar Partana, Crys (LPMPP Universitas Negeri Yogyakarta, 2008)
Recently, the qualityof education is still an urgent problem in the enhancementofthe quality of the national education system, especially in the improvement ofthe· classroom learning quality. One of the efforts to conduct learning activities inthe classroom ()ptimallyis· ... by .making learning methods varied. One learningmethod implemented in developed countries nowadays is the cooperative learningmethod, -namely a: method designed to make students work cooperatively ingroups· to solve the learning materials. There are five kindsof cooperative learningmethods, namely:1) Student Teams Achievement Division ·(STAD); 2) Team GameTournament (TGT);3) JigsawII; 4) Team Accelerated Instruction (TAl); ··and 5)Cooperative Integrated Reading and Composition(CIRC). The effectiveness of thecooperative methods was investigated by implementing the JigsawII and STADmethods in one of the natural science subjects, namely chemistry, in SMP 2 MlatiSleman. The methods were implementedin two experiment groups while aconventional method, consisting of the lecturing and question-answer techniques,was implemented in the control group. The Jigsaw II and STAD cooperativelearning methods were effective to improve learning achievement, learningmotivation, and learning activities in the classroom.